2013
DOI: 10.2337/dc12-0849
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cystatin C and Tubular Proteinuria Predict Progression of Diabetic Nephropathy

Abstract: OBJECTIVEThe aim of this study was to evaluate the association of urinary cystatin C, a tubular damage marker, with the progression of type 2 diabetic nephropathy.RESERCH DESIGN AND METHODSThe baseline values of serum and urinary cystatin C were measured as primary parameters and those of urinary nonalbumin protein (NAP) were measured as secondary parameters. In this prospective observational study, a total of 237 type 2 diabetic patients were followed up for 29 months (13–44 months).RESULTSBoth the urinary cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(106 citation statements)
references
References 32 publications
5
98
1
2
Order By: Relevance
“…In the diabetic patient group u-CYSC, data suggest that tubular damage has not been developed yet. Tubular damage might precede the appearance of microalbuminuria only in a few cases of diabetes where increased u-CYSC may be useful for the recognition of these patients [26]. Moreover, in certain cases with proteinuria it should be taken into consideration, that the competition between albumin and low molecular weight proteins for receptor-mediated reabsorption could elevate the urinary levels of CYSC as well [32].…”
Section: Preliminary Reference Ranges Patients' Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the diabetic patient group u-CYSC, data suggest that tubular damage has not been developed yet. Tubular damage might precede the appearance of microalbuminuria only in a few cases of diabetes where increased u-CYSC may be useful for the recognition of these patients [26]. Moreover, in certain cases with proteinuria it should be taken into consideration, that the competition between albumin and low molecular weight proteins for receptor-mediated reabsorption could elevate the urinary levels of CYSC as well [32].…”
Section: Preliminary Reference Ranges Patients' Datamentioning
confidence: 99%
“…Since spot urine samples were analyzed, it was reasonable to express results also as u-CYSC/u-CREAT ratio in order to exclude the effect of different hydration states (as it is reported by others) [4,8,[26][27][28]. However, it is future science group www.future-science.com known that in case of tubular damage the excretion of creatinine is also affected which may influence the urinary protein/u-CREAT values [29].…”
Section: Preliminary Reference Ranges Patients' Datamentioning
confidence: 99%
“…103 For cystatin C, its urinary excretion suggests tubular injury as it is elevated early in diabetes and prediabetic nephropathy, together with NGAL. 104 Besides the predictive role of urinary cystatin C for the progression of DN, 105 its serum and urinary levels are useful biomarkers for assessing early nephropathy in T2DM. 106 Although KIM-1, as tubular transmembrane glycoprotein, is a well-known sensitive biomarker for acute kidney injury, 107 increased urinary levels have been reported in normoalbuminuric T2DM patients, indicating lesions of the proximal tubule in early stages of the disease.…”
mentioning
confidence: 99%
“…They concluded that urinary cystatin C level may be valuable marker for detection of microalbuminuria independent on any other tubular markers and independent of the degree of tubular dysfunction, and that it can be used as a good predictor for the presence of microalbuminuria in early DN [45]. Another study from type 2 diabetic patients found that increased urinary cystatin C was associated with decline in GFR, particularly at the early stages of DN in patients with an eGFR of ≥60 mL/min/1.73 m 2 and was associated with progressed to CKD stage 3 or greater, which indicated that higher urinary cystatin C excretion was a better predictor of early nephropathy [46].…”
Section: Cystatin C As a Marker For Early Diabetic Nephropathymentioning
confidence: 99%